Strategies for the Surgical Treatment of Brachial Plexus Traumatic Injuries: A Survey among Neurosurgeons in Latin America - Siqueira, Mario Gilberto; Socolovsky, Mariano; Martins, Roberto Sergio; Di Masi, Gilda (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Peripheral nerve surgeons still disagree on the best moment to operate and on the best surgical strategy to employ in each clinical injury type of brachial plexus lesion. This study surveyed a specific group of neurosurgeons in Latin America to determine their reconstruction strategies for different brachial plexus injury cases.A survey was emailed to 46 neurosurgeons who operate at least 15 BPIs per year. The questionnaire was divided into ten questions based on general issues and four hypothetical clinical cases.There were 23 respondents from five countries, each one performing an average of 35.5 brachial plexus reconstructions annually. Surgery was indicated as soon as possible for Case 1 (adult with complete brachial plexus palsy), predominantly reconstruction with nerve transfers. The same was recommended for Case 2 (adult with C5-C6 lesion). In Case 3 (adult with C8-T1 lesion), most surgeons indicated that surgery should be performed as soon as possible, and nerve transfers should be used for plexus reconstruction. In Case 4 (infant with Erb́s palsy), 40% of the surgeons would operate within three months and 53.3% within six months after birth. Usually complemented by nerve transfers, grafts were chosen by 53.3% of the surgeons. Postoperative rehabilitation was inadequate in more than half of the patients (56.5%).The survey respondents had many agreements. Nevertheless, there is yet to be a complete consensus on the many persisting issues, and prospective randomized studies are needed to evaluate the merits of each surgical treatment strategy for BPI.
Keywords: brachial plexus surgery; Latin American neurosurgeons; survey; nerve transfers; adult brachial plexus injury; neonatal brachial plexus injury